2021
DOI: 10.1021/acscatal.0c04868
|View full text |Cite
|
Sign up to set email alerts
|

Stable Palladium Oxide Clusters Encapsulated in Silicalite-1 for Complete Methane Oxidation

Abstract: Zeolite-supported metal catalysts are widely employed in a number of chemical processes, and the stability of the catalytically active species is one of the most critical factors determining the reaction performance. A good example is the Pd/zeolite catalyst, which provides high activity for methane oxidation but deactivates rapidly under the reaction conditions due to palladium nanoparticle sintering. Although coating the metals with thin shells of porous materials is a promising strategy to address the sinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 63 publications
2
35
0
Order By: Relevance
“…Several research groups have adopted this synthesis procedure and showed that the encapsulated Pd nanoparticles are highly active for the complete oxidation of methane. [16,39,50,65] Figure 5 shows a schematic illustration of the so-called in situ synthesis using ethylenediamine. The figure also shows how Wang et al reduced their catalyst under H 2 in their original work.…”
Section: Materials Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…Several research groups have adopted this synthesis procedure and showed that the encapsulated Pd nanoparticles are highly active for the complete oxidation of methane. [16,39,50,65] Figure 5 shows a schematic illustration of the so-called in situ synthesis using ethylenediamine. The figure also shows how Wang et al reduced their catalyst under H 2 in their original work.…”
Section: Materials Synthesismentioning
confidence: 99%
“…High-silica zeolites with the MFI framework have recently received much attention, [15,16,39,50,65,80] which may be explained by the issues with water and increasing interest in hydrophobic properties. [18,[27][28][29] For example, silicalite-1 (S-1) is an MFI zeolite that contains no Al and, therefore, has no acidic sites but high hydrophobicity and hydrothermal stability.…”
Section: Zeolite Typementioning
confidence: 99%
See 3 more Smart Citations